(untitled) (Journal of Contemporary Philology, 2018)
The paper discusses the concessive constructions consisting of (verbal and qualifying) adjectives, nouns and verbal adverbs detached from the prosodic structure of the utterance. This paper focuses on several properties of these constructions: the information character and the position of the constructions, on the one hand, and the syntactic functions of the referents and their status regarding the opposition given vs. new information, on the other hand. The analysis is carried out on examples collected from literary works by several Macedonian writers.